Implementation of the Policy for Strengthening the Character Education of Formal Education Students in Bombana Regency - Ernawati, Ernawati; Asrun Azis R, Laode; Mulku Zahari, Ahmad Farouq; Azhari, Azhari; Firdaus, Firdaus (Universitas 17 Agustus 1945 Surabaya, 2024)
Character education is the key to improving student achievement. The achievements of students can make a name for themselves and increase the prestige of the school. However, currently there are still many problems with students that can tarnish the name of the school, family and student's future. Therefore, character education policies are really needed to shape students' character and behavior so that they can become high-achieving and well-behaved people. This research aims to determine the description of character education policy practices at North Poleang 20 Junior High School. This research uses a qualitative approach with a descriptive type where data is obtained from interviews, observations and collecting supporting documents. The results of this research show that character education policies are implemented by involving the roles of parents, teachers, students and the surrounding environment. This policy has a positive impact on student awareness and behavior even though there are still obstacles faced regarding the involvement of students' parents in understanding character education.